Bundle Care and Multidisciplinary Team Approach to Reduce Surgical Site Infections Risk: A Scoping Review - Yunita Dewi Indriani; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2023)
This scooping review aims to analyze a combination of bundle care and a multidisciplinary team approach to reduce Surgical Site Infection (SSI) in high-risk patients. The authors identified literature published between 2012 and 2021. The databases used to search for related journals included PubMed, Scopus, and EBSCO. PRISMA protocol will be used in this study. The review will include published papers discussing bundle care use and the multidisciplinary team approach which impacts SSI, especially in high-risk patients. Several studies showed a decrease in SSI rate in the intervention group that applied bundle care and a multidisciplinary team approach. Reducing SSI in patients with higher ASA (The American Society of Anesthesiologists) levels was even more significant.